2018
DOI: 10.1002/ecy.2147
|View full text |Cite
|
Sign up to set email alerts
|

Competitive ability, stress tolerance and plant interactions along stress gradients

Abstract: Exceptions to the generality of the stress-gradient hypothesis (SGH) may be reconciled by considering species-specific traits and stress tolerance strategies. Studies have tested stress tolerance and competitive ability in mediating interaction outcomes, but few have incorporated this to predict how species interactions shift between competition and facilitation along stress gradients. We used field surveys, salt tolerance and competition experiments to develop a predictive model interspecific interaction shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 44 publications
5
89
0
Order By: Relevance
“…For example, it has often been questioned whether the changes in the sign and frequency of plant–splant interactions across environmental gradients are driven by the environment itself, or by the changes in species composition along the studied gradients (e.g. Gross et al., ; Hacker & Gaines, ; Liancourt, Le Bagousse‐Pinguet, Rixen, & Dolezal, ; Qi et al., ; Soliveres & Maestre, ). Additionally, compositional shifts towards communities dominated by species specialized to thrive under arid conditions could make plant communities less sensitive to further increases in aridity (Ulrich et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has often been questioned whether the changes in the sign and frequency of plant–splant interactions across environmental gradients are driven by the environment itself, or by the changes in species composition along the studied gradients (e.g. Gross et al., ; Hacker & Gaines, ; Liancourt, Le Bagousse‐Pinguet, Rixen, & Dolezal, ; Qi et al., ; Soliveres & Maestre, ). Additionally, compositional shifts towards communities dominated by species specialized to thrive under arid conditions could make plant communities less sensitive to further increases in aridity (Ulrich et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…() found that, under drought conditions, two competitive grass species showed stronger facilitative response to neighbours than was the case for coexisting drought‐tolerant species. A similar result was found in more comprehensive experimental studies for plants grown along a salinity or pH gradient (He et al ., ; Qi et al ., ). In general, our findings are compatible with most previous studies and theoretical predictions about the trait dependence of facilitative response, although there is conflicting evidence as well (Donovan & Richards, ).…”
Section: Discussionmentioning
confidence: 97%
“…This has been confirmed by many empirical studies conducted in salt marshes and along other salinity gradients (Bertness, ; Bertness & Shumway, ). If shading was the main mechanism in our study, too, then facilitative effects should be size‐dependent, with large plants exhibiting a stronger facilitative effect than small plants (Qi et al ., ). This rationale had inspired our hypothesis about salt‐tolerant plants having a stronger facilitative effect than sensitive plants, because they are bigger under saline conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies suggest a decline in facilitation toward the most severe conditions, as facilitators are less successful in ameliorating stress in very harsh environments (Kawai and Tokeshi ; but see He and Bertness , Qi et al. ). Therefore, while the facilitation of mussels at 8 m depth increases with exposure throughout the wave exposure gradient (Fig.…”
Section: Discussionmentioning
confidence: 99%